1991
DOI: 10.1037/0012-1649.27.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Transition to parenthood in adoptive families.

Abstract: This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 28 publications
6
96
0
3
Order By: Relevance
“…As emerged in previous studies (Ceballo et al 2004;Judge 2003;Goldberg and Smith 2014;Palacios and Sanchez-Sandoval 2006), soon after placement adoptive parents reported low stress levels, even lower than those found in the normative Italian sample (Guarino et al 2008). As already suggested by Levy-Shiff et al (1991), new adoptive parents seem to experience a 'honeymoon' period: this transition appears to have fewer negative effects than it has on biological parents, possibly because years of longing make adoptive parents feel more gratified by the rewards accompanying their new status, while they tend to underestimate the difficulties of taking care of their children and interacting with them. Although research on adoptive parents' stress trajectories is conflicting, we can suppose that the levels of stress could increase in the following years, as evidenced in recent literature (Goldberg and Smith 2014), highlighting the importance of prevention efforts.…”
Section: Discussionmentioning
confidence: 85%
“…As emerged in previous studies (Ceballo et al 2004;Judge 2003;Goldberg and Smith 2014;Palacios and Sanchez-Sandoval 2006), soon after placement adoptive parents reported low stress levels, even lower than those found in the normative Italian sample (Guarino et al 2008). As already suggested by Levy-Shiff et al (1991), new adoptive parents seem to experience a 'honeymoon' period: this transition appears to have fewer negative effects than it has on biological parents, possibly because years of longing make adoptive parents feel more gratified by the rewards accompanying their new status, while they tend to underestimate the difficulties of taking care of their children and interacting with them. Although research on adoptive parents' stress trajectories is conflicting, we can suppose that the levels of stress could increase in the following years, as evidenced in recent literature (Goldberg and Smith 2014), highlighting the importance of prevention efforts.…”
Section: Discussionmentioning
confidence: 85%
“…Levy-Shiff, Goldshmidt, and Har-Even (1991) found that parental expectations and depressed mood were predictive of the transition to parenthood for both adoptive and biological parents. The strongest correlates for patemal postpartum depression were level of the mother's depression, the discrepancy between expectations and the reality of family and social life after the birth of tiie child, and low satisfaction with the marital relationship (Bielawska-Batorowicz & Kossakowska-Peti7cka, 2006).…”
Section: Conceptual Framework: Parental Expectationsmentioning
confidence: 99%
“…The aim of the interview was to broaden current knowledge and to think about fathering during pregnancy, by investigating how prospective fathers (as well as prospective mothers) are involved in the transition to fatherhood. In particular, the interview was aimed at detecting the possible existence of the highly nurturant and involved "new" father (Pruett, 1987;Russell, 1983) as opposed to the more traditional father (the disciplinarian and masculine breadwinner, the head of the household and family protector); and (c) to base the topic on the specific Italian context; recent literature has stressed how contextual factors are important determinants of parenthood (Belsky, 1984;Belsky, Herzog, & Rovine, 1985;Feldman & Nash, 1985), with emphasis on particular variables reflecting the larger social context in which parent -child dynamics are embedded, especially social support (Crnic et al, 1983;Levy-Shiff et al, 1991). Some of the questions in the interview schedule aimed at reflecting the psychological and social situation of Italian couples during pregnancy.…”
Section: The Interviewmentioning
confidence: 98%
“…It is a period of restructuring, transition, and a maturational crisis, associated with a significant alteration in life pattern and can cause profound personal, marital, familial, and social changes (Berman & Pedersen, 1987;Cath, Gurwitt, & Gunsberg, 1989;Levy-Shiff, Goldshmidt, & Har-Even, 1991;Michaels & Golberg, 1988;Palkovitz & Copes, 1988). In fact, the couple has to make room for a new member and create an adequate psychological space for him/her.…”
mentioning
confidence: 97%